Wanita : Ekuilibrium Antara Ideologi Weda Dan Realita Masa Kini - Kusumasanthi, Dewi; Suparta, Ida Kade (Widya Sandhi, 2023)
The views of several Hindu texts regarding the position of women are contradictory to the perspective of society, sometimes leading to criticism and unfavorable views on Hindu teachings. In fact, the status of women in the Vedic era was very special and noble but slowly degraded during the post-Vedic era and so on. This paper seeks to examine Vedic texts to provide an understanding of the position of women in the Vedic era in line with the demands of women's emancipation in modern times. The results showed that women, especially wives or mothers, were considered a symbol of the sanctity of the family and were highly respected because of their extraordinary role in continuing the family lineage, educating their children, practicing religion, and contributing to the development of the family and society. Kind, loyal, and well-educated personalities are the conditions laid down in the Vedic texts to actualize these roles. In terms of religious practice, women are positioned as central to the success of yajña.